Pembelajaran Sains dalam Pemulihan Learning Loss pada Anak Usia 5-6 Tahun di PG/TK Dunia Anak Cerdas Bandung - Hasna Afifah Nuraini; Dedih Surana; Nurul Afrianti (UNISBA Press, 2023)
Abstract. During the post-Covid-19 learning period, all educational institutions reviewed and redesigned the process of providing education from univertisy to early childhood education during the Covid-19 pandemic. The emergence of difficulties in the online learning process that takes too long can cause learning loss. Learning loss is a phenomenon where generetions lose the opportunity to acquire knowledge due to delays in the education and learninf process. This study used a qualitative approach with a descriptive study method using triangulation data collection techniques or combining several techniques, namely interviews, observation, and documentation. The research was conducted to find out the description of science learning in the recovery of learning loss in children aged 5-6 years at PG/TK World Smart Children Bandung. Based on the findings of the research data, it was concluded that the science learning plan in Smart Childrems World PG/Kindergarten includes the Semester Program, Weekly Learning Implementation Plan (RPPM), and Daily Implementation Plan (RPPH). Science learning is carried out 1 time in 1 week. The impact of the Application od science learning on the recovery if learning loss is found in children’s learning outcomes. Science learning activites that require large funds are an inhibiting factor in the implementation of science learning in the Smart Children’s World PG/Kindergarten because they need to wait for funds from the government, namely BOP funds. Abstrak. Pada masa pembelajaran pasca Covid-19, seluruh lembaga pendidikan mengkaji dan mendesain ulang proses penyelenggaraan pendidikan mulai dari universitas hingga pendidikan anak usia dini selama pandemic Covid-19. Munculnya kesulitan dalam proses pembelajaran daring yang terlalu lama dapat menyebabkan learning loss. Learning loss merupakan fenomena dimana generasi kehilangan kesempatan untuk memperoleh pengetahuan karena penundaan dalam proses pendidikan dan pebelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi deskriptif dengan menggunakan teknik pengumpulan data triangulasi atau menggabungkan beberapa teknik, yaitu wawancara, observasi, serta dokumentasi. Penelitian dilakukan untuk mengetahui gambaran pembelajaran sains dalam pemulihan learning loss pada anak usia 5-6 tahun di PG/TK Dunia Anak Cerdas Bandung. Berdasarkan hasil temuan data penelitian, didapatkan kesimpulan bahwa perencanaan pembelajaran sains di PG/TK Dunia Anak Cerdas meliputi Program Semester, Rencana Pelaksanaan Pembelajaran Mingguan (RPPM), dan Rencana Pelaksanaan Pembelajaran (RPPH). Pembelajara sains dilakukan sebanyak 1 kali dalam 1 minggu. Dampak dari penerapan pembelajaran sains terhadap pemulihan learning loss terdapat pada hasil capaian belajar anak. Kegiatan pembelajaran sains yang membutuhkan dana besar menjadi faktor pemhambat dalam pelaksanaan pembelajaran sains di PG/TK Dunia Anak Cerdas dikarenakan perlu menunggu dana dari pemerintah yaitu dana BOP.